2017
DOI: 10.3349/ymj.2017.58.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Serum Chemerin Levels are Associated with Visceral Adiposity, Independent of Waist Circumference, in Newly Diagnosed Type 2 Diabetic Subjects

Abstract: PurposeChemerin has been suggested to be linked to insulin resistance and type 2 diabetes mellitus (T2DM). However, the relationship between visceral adiposity and chemerin levels remains unclear in subjects with T2DM. In this study, we investigated the relationship between serum chemerin levels and visceral adiposity.Materials and MethodsThis study included 102 subjects newly diagnosed with T2DM. The relationships between serum chemerin levels and clinical and biochemical parameters were examined. Multiple li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
4
23
0
12
Order By: Relevance
“…(3,19,20) After the first laboratory analysis, some blood samples were insufficient to reveal the values of each variable that composed MC, requiring a new sample. However, due to the refusal of some participants to collect the blood material for the second time, in those cases where the first collection was not sufficient, some missing data may be observed in the results.…”
Section: Methodsmentioning
confidence: 99%
“…(3,19,20) After the first laboratory analysis, some blood samples were insufficient to reveal the values of each variable that composed MC, requiring a new sample. However, due to the refusal of some participants to collect the blood material for the second time, in those cases where the first collection was not sufficient, some missing data may be observed in the results.…”
Section: Methodsmentioning
confidence: 99%
“…A decade later, Treuth et al [87] showed evidence on the relationship of strength training with adiposity control and, consequently, obesity. After 16 weeks of exercise performed 3 times per week, the authors observed that although the body weight of participants was not changed, the amount of intra-abdominal adipose tissue was significantly reduced [88].…”
Section: Fructose Consumption and Its Complicatons: The Role Of Strenmentioning
confidence: 99%
“…A decade later, Treuth et al [87] showed evidence on the relationship of strength training with adiposity control and, consequently, obesity. After 16 weeks of exercise performed 3 times per week, the authors observed that although the body weight of participants was not changed, the amount of intra-abdominal adipose tissue was significantly reduced [88].Recent studies have provided us with a better understanding of how strength exercise is able to improve for glycemic control. A performed study which used obese animals and submitted them to strength exercise on staircase [89], besides confirming reductions in serum insulin levels showed that after 8 weeks of training some proteins from insulin pathway had increased their action, such as phosphatidylinositol 3-kinase (PI3-K) and Akt.…”
mentioning
confidence: 99%
“…Wykazywano wielokrotnie, że stężenie tej cytokiny jest istotnie większe u pacjentów z otyłością, cukrzycą typu 2 i chorobą niedokrwienną serca [18][19][20]. CHEM było zależne nie tyle od BMI badanych, co od ilości tkanki tłuszczowej trzewnej [21,22], a także -odwrotnie korelowało z insulinowrażliwością [23].Wysokie stężenie chemeryny może być markerem powikłań mikronaczyniowych cukrzycy -retinopatii i nefropatii [24,25].…”
Section: Dyskusjaunclassified